2023
DOI: 10.1152/ajplung.00086.2023
|View full text |Cite
|
Sign up to set email alerts
|

Loss of growth differentiation factor 15 exacerbates lung injury in neonatal mice

Abstract: Growth Differentiation Factor 15 (GDF15 ) is a divergent member of the TGF-β superfamily, and its expression increases under various stress conditions, including inflammation, hyperoxia, and senescence. GDF15 expression is increased in neonatal murine BPD models, and GDF15 loss exacerbates oxidative stress and decreases cellular viability in vitro. Our overall hypothesis is that the loss of GDF15 will exacerbate hyperoxic lung injury in the neonatal lung in vivo. We exposed neonatal Gdf15-/- mice and wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…For example, we noted decreased representation of transcriptional pathways in molecular function gene sets in Gdf15 −/− mice during PA SN injury ( Figure 6D ). Others have described similarly meaningful differences in transcriptional programs with genetic deficiency of GDF15 ( 46 , 48 ), and others have suggested that pro-GDF15 possesses a nonclassical nuclear localization sequence and can interact with Smad binding to DNA ( 49 ). Therefore, it remains poorly defined whether GDF15 may execute intracellular roles in the lung and what underlying mechanism(s) may account for any such roles, which are topics worthy of further investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, we noted decreased representation of transcriptional pathways in molecular function gene sets in Gdf15 −/− mice during PA SN injury ( Figure 6D ). Others have described similarly meaningful differences in transcriptional programs with genetic deficiency of GDF15 ( 46 , 48 ), and others have suggested that pro-GDF15 possesses a nonclassical nuclear localization sequence and can interact with Smad binding to DNA ( 49 ). Therefore, it remains poorly defined whether GDF15 may execute intracellular roles in the lung and what underlying mechanism(s) may account for any such roles, which are topics worthy of further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the difference in approach, there are similarities between our findings of decreased cytokine signaling in the airspaces during acute lung injury and the attenuation of lung fibrosis and fibroblast activation demonstrated in bleomycin-injured mouse lungs with neutralizing antibody–mediated GDF15 deficiency ( 44 ). To attempt to synthesize the possible roles for GDF15 in the lung during injury, we and others have noted lung epithelial expression of GDF15 ( 14 , 44 , 45 ), increased lung and lower respiratory tract levels during injury ( 44 , 45 ), increased plasma levels ( 14 ), and modulation of local and remote functions such as cytokine signaling, modulation of fibroblast and macrophage activation ( 44 , 46 , 47 ), and stress erythropoiesis ( 8 , 9 ). Further work is needed to understand the contribution of other cellular sources of GDF15 during pathogen injury such as lung endothelium and the mechanism(s) by which GDF15 may execute its roles.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 also associates with lung fibrosis. GDF-15-deficient neonatal mice, which were briefly exposed to hyperoxia, presented decreased survival rates along with impaired alveolarization and perturbed macrophage activation in lung tissue [129]. In a bleomycin-induced lung fibrosis mouse model, GDF-15 expression and protein levels are increased in lung tissue, bronchoalveolar fluid, and plasma of mice with pulmonary fibrosis.…”
Section: Fibrosismentioning
confidence: 98%